Selected Topics in Neonatal Care 2018
DOI: 10.5772/intechopen.69675
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Osteomyelitis

Abstract: Osteomyelitis in neonates is relatively uncommon, but burdened with an increased hospital stay and possible long-term sequelae if not diagnosed on time. It differs from that of older children for etiology, clinical and radiological findings, and treatment. Due to anatomic contiguity, osteomyelitis may coexist with septic arthritis. Soft-tissue swelling or joint effusion is often associated. Our aim is to review the literature to provide the most recent data related to epidemiology, clinical presentation, diagn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 52 publications
(50 reference statements)
1
6
0
Order By: Relevance
“…ICs have proven to be the major driver of LOS and costs in the NICU population. 15 Our study demonstrates that ICs have a major impact on LOS and costs for patients with both SG and CG. We found that specific IC influenced outcomes more than others.…”
Section: Discussionmentioning
confidence: 62%
“…ICs have proven to be the major driver of LOS and costs in the NICU population. 15 Our study demonstrates that ICs have a major impact on LOS and costs for patients with both SG and CG. We found that specific IC influenced outcomes more than others.…”
Section: Discussionmentioning
confidence: 62%
“…MRI has become the gold standard to evaluate musculoskeletal infection and the positive rate of MRI in detecting osteomyelitis was 100% (21). It has the capability of assessing the osseous, articular and muscular structures simultaneously and does not require ionizing radiation (18).…”
Section: Discussionmentioning
confidence: 99%
“…In some cases, post-natal surgical repair is suggested (2). Osteomyelitis in neonates is usually due to hematogenous spread of bacterial infections or less frequently to direct inoculation as a result of a trauma or surgery (18). Common symptoms include bone pain, swelling, redness, guarding and failure to move the affected body part (pseudoparalysis).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations